Diversity of Invasif Aliens Species in Sultan Thaha Saifuddin Grand Forest Park, Jambi - Nursanti, Nursanti; Adriadi, Ade (Media Konservasi, 2018)
Research on invasive plant diversity in Sultan Thaha Syaifuddin Forest Park area has been done from July - sepetember 2017 by quadratic method. The plot is placed by purposive sampling consisting of 52 plots with a plot size of 5m x 5 m. The result of this research showed that invasive plant composition was 7 families, 9 species and 1.775 individuals. Clidemia hirta has the highest important index value of 51.53% and Acacia mangium has the second highest important value index after Clidemia hirta is 34.46%. The diversity index of invasive plants is H ’= 1.8. Clidemia hirta is a weed and invasive plant growing on agricultural land, logged over and an aggressive pioneer species due to its rapidly germination of seeds, which invade open spaces, landslides, roadsides, paths, logged-over fields and humps forest and can grow fast and tolerant to shade. Acacia mangium is the second dominant species found after Clidemia hirta. Acacia mangium is known by the name of acacia, its rapid growth, good quality of wood and its tolerant ability to various kinds of soil and environment. Keywords: composition, invasive aliens species, structure